Crop production in Ethiopia: Regional patterns and trends: Summary of ESSP working paper 16 - Taffesse, Alemayehu Seyoum; Dorosh, Paul A.; Asrat, Sinafikeh (International Food Policy Research Institute, 2012)
This paper presents an overview of crop agriculture in Ethiopia, focusing mainly on cereal production. Ethiopia’s crop agriculture continues to be dominated by the country’s numerous small farms that cultivate mainly cereals for both own-consumption and sales. Five major cereals (teff, wheat, maize, sorghum, and barley) occupy almost three-quarters of total area cultivated. Much of the increase in crop production in the past decade has been due to increases in area cultivated. To what extent expansion can continue remains a question, therefore obtaining higher yield rates is the challenge of Ethiopia’s agricultural system.